Snow Sports Trauma and Safety 2017
DOI: 10.1007/978-3-319-52755-0_14
|View full text |Cite
|
Sign up to set email alerts
|

Snowsport Instructors: Their Actual Maximum Speeds, Their Estimation of Maximum Speed and Speed in Slow Zones, and Their Knowledge of Helmet Effectiveness

Abstract: Snowsport safety strategies include resort and equipment design, trail management, emergency response, and public education. Snowsport instructors are well placed to inform their students about snowsport safety both in the behavior they model and the information they provide. To contribute to the evidence-base of snowsport safety and helmet awareness, this research explores the actual and estimated maximal speeds of ski and snowboard instructors across a normal work-day as well as their knowledge of helmet eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…should take the necessary steps to make skiers aware of how speed increases the chances of suffering severer accidents and of the advantages of speed self-awareness, and to train them in speed estimation, which, in the words of Ruedl et al [ 16 , p.122] “could easily be integrated into ski education courses”. Besides, new GPS-based devices, such as smartwatches, navigators or googles, can help skiers to improve their ability to estimate speed and, in general, their understanding of their own behaviour [ 28 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…should take the necessary steps to make skiers aware of how speed increases the chances of suffering severer accidents and of the advantages of speed self-awareness, and to train them in speed estimation, which, in the words of Ruedl et al [ 16 , p.122] “could easily be integrated into ski education courses”. Besides, new GPS-based devices, such as smartwatches, navigators or googles, can help skiers to improve their ability to estimate speed and, in general, their understanding of their own behaviour [ 28 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, the study benefited from using GPS-based technology, which has been showed to be adequate for snow-sports speed measurements [26,27]. It consisted of a smartphone new GPS-based application that provided advantages in terms of flexibility, affordability, and simplicity of operation or public accessibility compared to the radar guns that were previously used for measuring on-slope speed [25]. In general terms, the main results of this research were that all the individual factors under study seem to affect the actual speed of recreational adult snowboarders, and that snowboarding actual speed, gender, skill level and age seem to affect snowboarders' ability to estimate their actual maximum speeds, whereas risk-taking behaviour does not.…”
Section: Discussionmentioning
confidence: 99%
“…Speed measurements were gathered in different environmental conditions and at different times by a team of experienced snowboard instructors in their normal day's instructional activity [25]. Each was furnished with a smartphone preloaded with a recent (December, 2019) version of a GPS-based snow-sports application for Android (Ski Tracks 1.3.17; Core Coders Ltd.), previously and satisfactorily used in snow sports speed measurements and which, among other variables (altitude, number of runs, slope inclination, route followed, etc.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations